Policy Brief on Age Management: Ergonomic aspects and health interventions for older workers - Monika Bediova; Aneta Krejcova; Jiri Cerny; Andrzej Klimczuk; Juraj Mikus (National University of Ireland, Galway, 2019)
Globally, the population is ageing, which has serious consequences for businesses. The prosperity of companies is crucially dependent on the ability to effectively manage their employees, including older workers. Best practice in age management is defined as those measures that combat age barriers and/or promote age diversity. These measures may entail specific initiatives aimed at particular dimensions of age management; they may also include more general employment or human resources policies that help to create an environment in which individual employees can achieve their potential without being disadvantaged by their age (Walker, 1999). Promoting early retirement is generally not encouraged. Companies now have to encourage longer working lives. Much needs to be done to ensure that work remains a positive experience for workers throughout their career trajectories, and it does not damage their health. It has been found by studies that health is significantly related to retirement timing (both planned and unplanned) (Goyer, 2013, Adams et al., 2014), influences work performance (Merrill et al., 2012; Ilmarinen, 2009), and health-related organisational policies can positively influence employee retention (Towers, 2005). The major contemporary challenges to health at work are those associated with the way work, and work organisations are designed and managed. This is especially true for older workers. A comprehensive and effective approach towards age management can be very beneficial for them. How should companies implement age management? Some possible ways are set out in this policy brief below, which focuses on best practices in age management regarding ergonomic aspects and health interventions for older workers at an organisational level. The intention is to discuss the current situation and to illustrate some organisational techniques in selected countries. This policy brief can serve as an inspiration for, among others, companies and policymakers. Recommendations for successful practice are included. In total, this policy brief covers 8 COST member countries (the Czech Republic, Finland, Germany, the Netherlands, Slovenia, Spain, Sweden and the United Kingdom) to give a glimpse of the current situation of best practice in age management and show how companies in various states deal with ergonomic aspects, health interventions and the ageing of their labour force.
Keywords: J14; O15; 330; Age Management; Ergonomy; health interventions; older workers